Natural food flavors and colorants - Attokaran, Mathew (Wiley-Blackwell, 2017)
"The market for fully natural food products continues to grow, driving an increased interest in food additives derived from biological sources. In this book the author utilizes his over fifty years of experience in food chemistry and technology in order to produce the most detailed and comprehensive guide on natural food flavors and colors. Second edition has been fully updated, including two new chapters on Colored Vegetables and Stevia. Divided into three parts, Part I of the book begins with analysis, general properties and techniques. Regulatory information on synthetic colors in food will be very useful. Part II describes the various natural flavors and colorants that are available, alphabetized for convenient reference and including all the relevant recent developments since the publication of the first edition. Both the researchers and manufacturers will find FCC description of many products and the Identification numbers of regulatory bodies most valuable. Part III examines the future prospects of research and manufacture. Finally a well prepared Index will be of immense value to readers for getting a quick explanation and understanding of the various compounds, techniques and subjects covered. In particular, this guide will be of use to researchers, teachers, regulators, formulators and manufacturers of food"- Resumé vydavatel by publisher.
Keywords: potraviny; potravinářská chemie; potravinářská technologie; přírodní barviva; foodstuffs; food chemistry; food technology; natural dyestuffs; monografie; elektronické knihy; monographs; electronic books